2013
DOI: 10.1002/jgra.50383
|View full text |Cite
|
Sign up to set email alerts
|

Saturn suprathermal O2+ and mass‐28+ molecular ions: Long‐term seasonal and solar variation

Abstract: Suprathermal singly charged molecular ions, O2+ (at ~32 Da/e) and the Mass‐28 ion group 28M+ (ions at ~28 Da/e, with possible contributions from C2H5+, HCNH+, N2+, and/or CO+), are present throughout Saturn's ~4–20 Rs (1 Saturn radius, Rs = 60,268 km) near‐equatorial magnetosphere from mid‐2004 until mid‐2012. These ~83–167 keV/e heavy ions measured by Cassini's CHarge‐Energy‐Mass Spectrometer have long‐term temporal profiles that differ from each other and differ relative to the dominant water group ions, W+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 109 publications
0
35
0
Order By: Relevance
“…for pH 5 9 and 10, respectively). The mass resolution of Cassini instruments cannot distinguish between HCNH 1 , CO 1 , N 2 1 or Si 1 , and therefore no solid conclusion can be drawn for the origin of the mass 28 ions at the current stage 52 . The sputtering yield of Si-water ice mixture is unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…for pH 5 9 and 10, respectively). The mass resolution of Cassini instruments cannot distinguish between HCNH 1 , CO 1 , N 2 1 or Si 1 , and therefore no solid conclusion can be drawn for the origin of the mass 28 ions at the current stage 52 . The sputtering yield of Si-water ice mixture is unknown.…”
mentioning
confidence: 99%
“…Nonetheless, the presence of nanosilica particles and ice grains forming from hydrothermal fluids surely will supply the magnetosphere with silicon ions. Future modelling efforts should focus on the ionization, ion lifetime and acceleration processes that may be responsible for the enhanced ratio of 28 M 1 to water-group ions, (3-7) 3 10 23 , at the 100 keV energy level 52 . Sample size.…”
mentioning
confidence: 99%
“…We also showed that there was a steep drop in O 2 + density, as well as in the total heavy ion thermal plasma, over that time period. Consistent with this, the Magnetospheric Imagining Instrument (MIMI) recently reported a decrease from SOI through 2010 in energetic O 2 + density as compared to the W + density, followed by a recovery in 2011-2012 (Christon et al, 2013, submitted for publication). More recently a seasonal variation was reported for equatorial electron densities measured by the Radio and Plasma Wave Instrument (RPWS) .…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 66%
“…4. Although there will be no new data from the CAPS instrument to follow the growth to northern solstice, this interpretation appears to be supported by MIMI observations of energetic heavy ions (Christon et al, 2013, submitted for publication) and by the electron data . However, with the limited number of orbits in the region from 2.4 to 3.8R S that have good data, other interpretations are possible and the relative importance of the ring atmosphere and solar activity needs to be explored further.…”
Section: Discussionmentioning
confidence: 94%
“…Johnson et al () computed a photolytic flux of 10 6 /cm 2 s for neutral O 2 emission from the rings from solar ultraviolet irradiation but found the radiolytic flux from GCR interaction products to be an order of magnitude lower. However, strong seasonal variability up to several orders of magnitude (Christon et al, , ; Elrod et al, , ) of the magnetospheric O 2 + and other heavy ion population beyond the rings argues against the GCR energy source that varies only slightly over decadal time scales at energies above 20 GeV. Roussos et al () report long‐term changes of CRAND proton fluxes by less than a factor of 2 during the Cassini mission; the GCR flux at the ring neutron source for CRAND in the radiation belts would vary comparably.…”
Section: Discussionmentioning
confidence: 99%